Is Fusarium meridionale more adapted as Gibberella Ear and Stalk Rot pathogen of maize than F. graminearum? Comparative epidemiology and toxigenicity - Machado, Franklin Jackson (2019)
Gibberella ear (GER) and stalk rot (GSR) diseases of maize in Brazil are caused mainly by Fusarium meridionale, a species belonging to the Fusarium graminearum species complex (FGSC). Another species within this complex, F. graminearum, is second in importance on maize but is the main species causing Fusarium Head Blight disease of wheat in Brazil. This species is also the predominant cause of GER and GSR in North America, where F. meridionale has never been found. One hypothesis for the observed shift in dominance on different hosts where these species co-occur is that F. meridionale is more fit and adapted on maize than F. graminearum, and vice-versa. We undertook a thorough comparative analysis of pathogenic and saprophytic fitness- related traits using a collection of strains representative of the two species and hosts of origin in order to test this hypothesis. First, four field trials were conducted at different locations and hybrids to compare the aggressiveness (measure of GER severity) of two F. meridionale and two F. graminearum strains, all isolated from maize, inoculated singly or sequentially and alternately at the silking stage. Overall, GER severity was highest in plants inoculated with F. meridionale alone (52.1%); intermediate when inoculation with F. meridionale was followed by F. graminearum (Fmer⇾Fgra, 40.3%) or when F. graminearum was followed by F. meridionale (Fgra⇾Fmer, 38.3%); and lowest in plants inoculated with F. graminearum alone (23.8%). Only nivalenol (NIV) mycotoxin was detected in kernels from F. meridionale inoculations, and deoxynivalenol (DON) was the only mycotoxin found in F. graminearum inoculations. Approximately equal amounts of NIV and DON (1.2:1), along with zearalenone (ZON), were found in Fmer⇾Fgra, but only NIV could be detected in the Fgra⇾Fmer treatments. These results suggested that F. meridionale was more aggressive to maize than F. graminearum. However, this experiment included only a small number of isolates and so in a second study we used a much larger sample comprised of 16 isolates of F. graminearum (12 from wheat, four from maize), and 25 isolates of F. meridionale (nine from wheat, 16 from maize) to inoculate maize ears and stalks in the field. Field trials with four commercial maize hybrids were conducted during the winter and the summer growing seasons in Viçosa, MG. The host of origin made no difference in GER or GSR severity caused by isolates of either species. However, F. meridionale isolates were twice as aggressive as F. graminearum isolates infecting ears, while F. graminearum was, on average, slightly more aggressive on maize stalks than F. meridionale, regardless of the hybrid. Around half of F. graminearum strainsproduced primarily DON and 15ADON, whereas two thirds of F. meridionale strains produced only NIV. Mycotoxins were not detected in the remaining samples. In a third study, a slightly expanded collection consisting of 18 F. graminearum isolates (12 from wheat and six from maize) and 27 F. meridionale isolates (nine from wheat and 18 from maize) were compared in relation to 17 different saprophytic, pathogenic, and toxigenic traits. Although there was significant intraspecies variation for most traits, the strains were strongly structured by species regardless of the host of origin, based on a multivariate analysis. Results showed that F. graminearum was a more aggressive pathogen of wheat and produced higher numbers of macroconidia, perithecia, and ascospores in culture. All F. graminearum strains produced primarily DON in rice cultures or in wheat heads. On the other hand, F. meridionale was a more aggressive colonizer of maize silks and grew faster in culture. All F. meridionale strains produced mainly NIV both in vitro and in planta, with the exception of two strains from maize that produced more DON in wheat heads. The results of this study contribute new data on the biology of these species in subtropical and tropical conditions in Brazil. They suggest that differential aggressiveness and toxigenicity as partial explanations for the predominance of F. meridionale on maize and F. graminearum on wheat, and they lay a foundation for developing further hypotheses to explain these associations. Keywords: Triticum aestivum. Zea mays. Fusarium head blight. Nivalenol. Deoxynivalenol